PERAN DEWAN PERS SEBAGAI LEMBAGA NEGARA INDEPENDEN YANG MENJAMIN BERITA YANG LAYAK BAGI PERLINDUNGAN ANAK - Laurensius Arliman S (Mahkamah : Jurnal Kajian Hukum Islam, 2019)
Freedom of expression is one part of human rights. In Indonesia as a country of law and democracy, the right of expression has been set in the constitution. Article 28 letter G of the Constitution of the Republic of Indonesia Year 1945 states that the State protects the freedom of the press and freedom of expression. But freedom of the press in conveying information to the public contrary to the legal interest in ensuring the protection of children's rights. Children's right to protection and guarantee of media coverage that guarantees the confidentiality of information of children when dealing with the law, the presentation of news about the child should be better and benefit, the information presented should protect children. When the children read the information in the electronic or print media, so your child can easily understand the information. Law No. 40 of 1999 concerning the Press indepeneden produce a state agency called the Press Council, the Press Council should control the news related to the rights of children, which is accessed by the whole society. The role of the Press Council in protecting the rights of children is to supervise and control the news about the child, the Press Council puts journalist organizations as partners in the enforcement of the code of conduct. Moreover, sanctions on journalists who violate the code of conduct can only be given by an organization of journalists and press companies. Journalist organizations can follow up the assessment and recommendation of the Press Council against unethical reporting.